PENGIMBASAN KETAHANAN RHIZOCTONIA BINUKLEAT TERHADAP CEKAMAN AIR PADA BIBIT VANILI (Vanilla Planifolia ANDREWS) - DARYANTI DARYANTI; HARYUNI HARYUNI; DWI SUSILO UTAMI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2014)
The study, effect of Rhizoctonia binucleat resistance to water stress in seedlings of vanilla (Vanilla planifolia Andrews). This study aimed to determine the ability of thevanilla plant water stress situation with Rhizoctonia binucleat inoculated 30 days afterplanting. The study was conducted at the Faculty of Agriculture, University of wireSurakarta Development Branch. It was designed with a factorial randomizeds design consisting of 2 factors. The first factor Rhizoctonia binucleat inoculation (R) cedar there is no inoculation Rhizoctonia binucleat (R0) and inoculation with Rhizoctonia binucleat (R1). Inoculation was performed after 30 days of planting. The second factor sprinkling water treatment interval (A), consisting of daily watering (A1), 5 days (A2), every 10 days (A3), every 15 days (A4), and every 20 days (A5) . The results showed that the plants were inoculated with Rhizoctonia binucleat better growth and lower percentage of injury plant compared to plants without inoculation of Rhizoctonia binucleat.I